2015
DOI: 10.7883/yoken.jjid.2014.062
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Immunological Discordance in HIV-Infected Patients Receiving Antiretroviral Therapy with Complete Viral Suppression in a Resource-Limited Setting

Abstract: SUMMARY:``Immunological discordance,'' i.e., immunological failure despite complete viral suppression in human immunodeficiency virus (HIV)-infected patients receiving antiretroviral therapy (ART), is associated with increased risk of AIDS or death. To evaluate risk factors for immunological discordance in a resource-limited setting in which patients usually present late with low CD4 cell counts, we conducted a case-control study among HIV-infected patients receiving ART and having undetectable HIV RNA. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(12 reference statements)
1
3
0
Order By: Relevance
“…Immunological discordant responses was also associated with low CD4+ count (< 100 cells/μl) at baseline ( p = 0.026). Association of baseline CD4+ count with immunological discordance was also reported by studies conducted in Nigeria [ 7 ], Oman [ 12 ], Canada [ 27 ], India [ 9 ], Thailand [ 14 ], Italy [ 10 ] and China [ 26 ]. This may be related with diminution of CD4+ cells before initiation of antiretroviral therapy [ 27 ], which may be slow to reconstitute with antiretroviral therapy.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Immunological discordant responses was also associated with low CD4+ count (< 100 cells/μl) at baseline ( p = 0.026). Association of baseline CD4+ count with immunological discordance was also reported by studies conducted in Nigeria [ 7 ], Oman [ 12 ], Canada [ 27 ], India [ 9 ], Thailand [ 14 ], Italy [ 10 ] and China [ 26 ]. This may be related with diminution of CD4+ cells before initiation of antiretroviral therapy [ 27 ], which may be slow to reconstitute with antiretroviral therapy.…”
Section: Discussionsupporting
confidence: 61%
“…Immunological discordance among people living with HIV have been reported from 13.59 to 29% [ 5 – 13 ]. Factors such as being younger age [ 6 ], poor HIV treatment adherence, being male gender, lower baseline CD4+ count [ 2 , 7 , 9 , 14 ], not taking treatments from three antiretroviral classes [ 15 ], and Hepatitis C co-infection [ 10 ] have been reported to increase risk of immunological discordant responses. In other hand, virological discordant response has also reported from 5 to 17% [ 5 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from a previous study have confirmed that low baseline CD4 cell count, particularly < 100 cells/mm 3 , and history of loss to follow-up are risk factors for immunological discordance [ 18 ]. Independent risk factors associated with virological failure were being followed-up at the semirural center, having experienced unstructured treatment interruptions, and having low CD4 counts at enrolment [ 19 ].…”
Section: Introductionmentioning
confidence: 99%